A current history's disciplinary status in Britain in the first half of the twentieth century - Ганцян, Р. (Київський національний університет імені Тараса Шевченка, 2013)
The report is devoted to investigation of the current history's disciplinary status in Britain in the first half of the twentieth century and definition of It's object.

Доповідь присвячена дослідженню дисциплінарного статусу історії сучасності у Британії у першій половині ХХ ст. та визначенню об'єкта її розгляду.
Дисциплінарний статус історії сучасності у Британії у першій половині ХХ ст.
Keywords: Great Britain; current history; status; Велика Британія; історія сучасності; статус